Dataset on genetic and physiological adults׳ responses to social distress - Bonassi, Andrea (2018)
Both expectations towards interactions with conspecifics, and genetic predispositions, affect adults׳ social behaviors. However, the underlying mechanisms remain largely unknown. Here, we report data to investigate the interaction between genetic factors, (oxytocin receptor (OXTR) and serotonin transporter (5-HTTLPR) polymorphisms), and adult interactional patterns in shaping physiological responses to social distress. During the presentation of distress vocalizations (cries of human female, infants and bonobos) we assessed participants׳ (N = 42 males) heart rate (HR) and peripheral nose temperature, which index state of arousal and readiness to action. Self-reported questionnaires were used to evaluate participants’ interactional patterns towards peers (Attachment Style Questionnaire, Feeney et al., 1994[1]), and the quality of bond with intimate partners (Experiences in Close Relationships Scale, Fraley et al., 2000 [2]). To assess participants׳ genetic predispositions, the OXTR gene (regions rs53576, and rs2254298) and the 5-HTTLPR gene (region SLC6A4) were genotyped. The data set is made publicly available to enable critical or extended analyzes.